HIV/AIDS: Traditional Healers, Community Self-assessment, and Empowerment - Naur, Maja (World Bank, Washington, DC, 2012)
Most African countries have ratified the African Charter on Human and People's Rights, which states the rights to health, education, and promoting, safeguarding, and reinforcing mutual respect and tolerance. In Sub-Saharan Africa alone, some 17.2 million have died of HIV/AIDS. The focus here is, therefore, on how traditional healers and indigenous knowledge can empower communities to deal with the social consequences of the pandemic, and, at the same time, be able to ensure that government resources are actually being used to their benefit. This Notes suggests a mini epidemiological study be undertaken by community member and for the community. The process of community-managed research could be facilitated by traditional healers, local NGOs to balance any attempt by local elites to dominate the process.